Hedonic Responses to Touch are Modulated by the Perceived Attractiveness of the Caresser. (1st June 2021) - Novembre, Giovanni; Etzi, Roberta; Morrison, India
Highlights: Touch is perceived as more pleasant when caressing touch is paired with attractive, compared to unattractive, faces. Attractive faces particularly enhance subjective and autonomic responses to slow caresses. Heart rate variability increases only for slow touch paired with attractive faces. Abstract: Previous research has shown that a specific type of C fiber, the C tactile afferents, are involved in detecting gentle, dynamic tactile stimuli on the skin, giving rise to affective responses in the central nervous system. Despite building on such bottom-up information flow, the hedonic perception and the physiological consequences of affective touch are influenced by various sources of top-down information. In the present study we investigated how perception of affective touch is influenced by the attractiveness of hypothetical caressers. Participants were stroked on the arm and the palm while looking at photos of high attractive and low attractive opposite-gender faces, and were instructed to imagine those people as the caressers. In a control condition no photo was paired with the touch. The stroking stimulation was delivered with a soft brush either on the forearm or on the palm, and either with a slower or faster speed. Participants rated the pleasantness of each stimulation, while electrocardiographic recordings were made to extract heart rate variability data. Results showed that participants preferred touch stimuli paired with high attractive faces; they also preferred palm stroking and slower stroking speed. Like subjective pleasantness ratings, heart rate variability responses to affective touch (slow) were higher for high attractive than for low attractive caressers, but were not selective for arm or palm stroking. Overall, the present study confirms that contextual social information plays a major role in affective touch experiences, influencing not only the hedonic quality of the experience but also the physiological state of the body.